1998
DOI: 10.1007/s002449900426
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 14 Elements in Tissues and Organs of Oceanic Seabirds

Abstract: The concentrations of 14 trace elements (Li, V, Mn, Co, Cu, Zn, Se, Rb, Sr, Ag, Cd, Cs, Pb, and Hg) were determined in tissues and organs of three species and in the liver of 11 species of seabirds. Comparatively high concentrations of Li, Co, Sr, and V were found in the femur. Cd, Se, Cu, and Mn concentrations were relatively higher in the kidney than in other tissues and organs. Rb, Cs, and Pb concentrations were rather uniform among tissues. Concentrations of essential elements such as Mn, Cu, and Co were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
51
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 24 publications
17
51
3
Order By: Relevance
“…Only in the tropicbirds did juveniles have higher essential metal levels than adults. This same pattern has already been observed in various species (Kim et al 1998, Stewart et al 1999 in which the young accumulate essential elements to meet particularly high nutritional needs (Thompson et al 1996). This strategy may have evolved in order to survive the fast caused by the abandon of the fledglings by their parents several days before their first flight.…”
Section: Influence Of Phylogenysupporting
confidence: 77%
See 3 more Smart Citations
“…Only in the tropicbirds did juveniles have higher essential metal levels than adults. This same pattern has already been observed in various species (Kim et al 1998, Stewart et al 1999 in which the young accumulate essential elements to meet particularly high nutritional needs (Thompson et al 1996). This strategy may have evolved in order to survive the fast caused by the abandon of the fledglings by their parents several days before their first flight.…”
Section: Influence Of Phylogenysupporting
confidence: 77%
“…There are few data on the distribution of Mn among seabird tissues. It was found mainly in the liver and kidney of Procellariiformes studied by Kim et al (1998) and mainly in the liver of Reunion birds. Further studies are needed to determine the bioaccumulation pattern of Mn in seabird tissues.…”
Section: Relationships Between Trace Element Levelsmentioning
confidence: 95%
See 2 more Smart Citations
“…Even though a high concentration of Hg is expected in such predatory seabirds, our results seem to corroborate the earlier study on gannets with respect to the above-mentioned potential Hg pollution. In general the relative differences between the values presently reported and those from birds evaluated by Mendes et al (2008) may result from a different use of food resources, considering diet's confirmed role as a major contamination pathway in marine vertebrates (Kim et al 1998). …”
Section: Discussionmentioning
confidence: 92%